A network analysis of carbon emission flows among marine industries in China - Wang, Lili; Zhou, Xinli; Wei, Liping; Xiao, Wenwen (Frontiers in Energy Research, 2023)
Based on the inter-industrial linkage such as techno-economic, the flow of products brings about the inter-industrial transfer of carbon dioxide. China's marine economy is growing rapidly and becoming more and more important in the national economy, so the carbon emissions caused by marine industries cannot be ignored. For this reason, this paper adopts industrial value added as the splitting weight, extracts 12 marine industries from the national industry classification, calculates the inter-industry carbon transfer coefficients, screens the strong correlation edges using the Weaver-Thomas combination index, and constructs a marine industry carbon transfer network. Based on the carbon transfer coefficient and degree, centrality, basic association tree and other network indicators to study the structural characteristics of carbon transfer. This paper identifies the key nodes in the network, analyzes their roles and functions in the network, and puts forward some suggestions for carbon reduction, which can help the effective implementation of carbon reduction measures. The results show that the electricity and heat production and supply industry is the most important industry in the carbon transfer network, and the effect of controlling the carbon emissions of this node will affect the neighboring industries. In addition, most of the marine industries in the network are carbon inflow industries with almost no emissions of their own, and emission reduction should be considered from their upstream industries.